2017
DOI: 10.1155/2017/5913041
|View full text |Cite
|
Sign up to set email alerts
|

K-Means Cluster for Seismicity Partitioning and Geological Structure Interpretation, with Application to the Yongshaba Mine (China)

Abstract: Seismicity partitioning is an important step in geological structure interpretation and seismic hazard assessment. In this paper, seismic event location ( , , ) and Euclidean distance were selected as the -Means cluster, the Gaussian mixture model (GMM), and the self-organizing maps (SOM) input features and cluster determination measurement, respectively, and 1516 seismic events ( > −1.5) obtained from the Yongshaba mine (China) were chosen for the cluster analysis. In addition, a Silhouette and Krzanowski-Lai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Morales-Esteban et al [10] proposed an efficient adaptive Mahalanobis-based K-means algorithm and this has been applied to study the seismic catalogues of Croatia and the Iberian Peninsula. Shang et al [11] proposed a Krzanowski-Lai and Silhouette combined index to select the optimum number of clusters for K-means and they interpreted the geological structure in the Chinese Yongshaba mine. The K-means cluster is useful for a large dataset cluster, and some studies have been done to reduce the effect of initial cluster centers.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Morales-Esteban et al [10] proposed an efficient adaptive Mahalanobis-based K-means algorithm and this has been applied to study the seismic catalogues of Croatia and the Iberian Peninsula. Shang et al [11] proposed a Krzanowski-Lai and Silhouette combined index to select the optimum number of clusters for K-means and they interpreted the geological structure in the Chinese Yongshaba mine. The K-means cluster is useful for a large dataset cluster, and some studies have been done to reduce the effect of initial cluster centers.…”
Section: Related Workmentioning
confidence: 99%
“…Besheli et al [21] performed a K-means clustering along with a SOM on an Iranian foreshock database and they found a foreshock zone which has a very close relation with large earthquakes. Nonetheless, research results [11,22] have shown that the SOM clustering may only be valid for high seismic activity areas, while for low seismic activity zones it may have bad cluster results. Furthermore, the SOM clustering may have discontinuous zones, which makes it hard to interpret cluster results [11,22].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations